Bibliometric Analysis Of Research Trends On Air Pollution And Its Impact On Brain Health, 2013–2023 - As, Zufikar Ali; Suhartono, Eko; Pahruddin, Muhammad (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
This study analyzes global trends related to the impact of air pollution on brain health using the bibliometric method. Data was collected from the Scopus database with the keyword "air pollution AND brain health" in the 2013–2023 time frame, resulting in 200 publications that were analyzed using Harzing's Publish or Perish and visualized with VOSviewer. The analysis shows that the United States, China, and several European countries dominated the research contribution, with a significant increase in publications in 2020 and 2021. Keyword visualization identified key themes, including the impact of fine particulate matter (PM2.5) on the risk of neurological disorders such as dementia and Alzheimer's, as well as the link between air pollution and brain inflammation and mental health. Although this issue is increasingly relevant globally, similar research in Indonesia is still very limited, especially regarding the direct impact of air pollution on brain health. These limitations create significant opportunities for further studies focusing on Indonesia's population, especially in cities with high pollution levels. This study provides in-depth insights into the direction of global research and highlights the need for further studies in Indonesia, which can contribute to the development of evidence-based environmental health policies to reduce the impact of pollution on public health.